2022
DOI: 10.1108/lht-04-2022-0200
|View full text |Cite
|
Sign up to set email alerts
|

Overview of herbal therapy of acute and chronic pulmonary disease: a conceptual map

Abstract: PurposeAcute and chronic obstructive pulmonary disease (COPD) is a common and progressive lung disease that makes breathing difficult over time and can even lead to death. Despite this, there is no definitive treatment for it yet. This study aims to evaluate the studies on single and combined herbal interventions affecting COPD.Design/methodology/approachIn this study, all articles published in English up to 2020 were extracted from the Web of Science (WoS) database and collected using Boolean tools based on k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Regarding healthcare, Borgohain et al (2024a) conducted a bibliometric investigation on mucormycosis, a fungus that evolved as a post-COVID-19 complication globally, to reveal the related research hot spots to inform researchers, policymakers and scientists. Balaei-Kahnamoei et al (2024) conducted a bibliometric analysis related to lung disease and found an upward trend from 1984 to 2021, with a surge in 2013. Tyagi (2024a) sketched the global research landscape of India's National Institute of Pharmaceutical Education and Research (NIPER) with bibliometrics to reveal the research trends and collaborative practices of NIPER's researchers.…”
Section: Healthcarementioning
confidence: 99%
“…Regarding healthcare, Borgohain et al (2024a) conducted a bibliometric investigation on mucormycosis, a fungus that evolved as a post-COVID-19 complication globally, to reveal the related research hot spots to inform researchers, policymakers and scientists. Balaei-Kahnamoei et al (2024) conducted a bibliometric analysis related to lung disease and found an upward trend from 1984 to 2021, with a surge in 2013. Tyagi (2024a) sketched the global research landscape of India's National Institute of Pharmaceutical Education and Research (NIPER) with bibliometrics to reveal the research trends and collaborative practices of NIPER's researchers.…”
Section: Healthcarementioning
confidence: 99%
“…They discovered 14 research topics in this area which can help specialists in health and medical areas to grasp the structured morphology of the current COVID-19 research. Readers may also notice our wealth of articles on bibliometrics related to COVID-19 (Li et al ., 2021a; Shueb et al ., 2022; Loan and Shah, 2022; Riahinia et al ., 2022; Zhu and Lei, 2022; Danesh et al ., 2021; Saab et al ., 2021; Allen, 2021; Yari Eili and Rezaeenour, 2023; Nadi-Ravandi and Batooli, 2023) and healthcare (Balaei-Kahnamoei et al ., 2022).…”
Section: Bibliometric Analytics For Research Topicsmentioning
confidence: 99%